Lesões bucais em pacientes idosos: estudo retrospectivo de 838 casos diagnosticados e registrados no laboratório de patologia bucal da Universidade Federal de Uberlândia-MG-Brasil - Costa Junior, Gabriel Tadeu (2007)
The proportion of older people is growing faster than any other age group. Due to that, there is a growing interest in the oral health status of older people as the size of this population is increasing around the world. It must be remembered that oral mucosa shows essential functions that significantly affect patient general health. With aging process the oral mucosa becomes more susceptible to external stimuli in function of a reducing capacity epithelium regeneration and consequently expose the individual to various harmful and infectious agents coming trough oral cavity. These predisposing factors are alcohol, tobacco, medicaments, nutritional deficiency, chronic diseases, prostheses and infectious agents. However there are unlimited studies in the world mentioning the prevalence of oral mucosal lesions in elderly that have been essentially of clinical nature. Surveys about alterations which the diagnoses have been made by histopathologic exams have been seldom mentioned. The aim of this study was to achieve a cross-section epidemiologic study of elderly oral disease, basing on a survey of diagnosed cases on the Oral Pathology Laboratory of the Universidade Federal de Uberlandia between 1978 and 2006. In order to that, 8837 registered cases in the lab archives were investigated on this period (28years). From the entire sample, 9,5% of the cases, corresponding 838 biopsies, satisfy the 60 69 years, 70 -79 years, 80 89 years and 90 or more years of age and oral tissues location criteria. For the classification Neville et al,,., (2002) criteria were used with modifications, assembling into twelve categories. The results show the majority cases are concentrated on the youngest group, 60-69 years (514/838), female the gender most affected (470/838) and alveolar edge the most common location (125/838). The twelve categories identified on this sample presented the follow frequency: Infectious diseases (2,6%), proliferative non neoplasic lesions (36,5%), bone lesions (2,6%), benignant and malignant neoplasms (22,4%), cysts and odontogenic tumors (3,0%), non odontogenic cysts (1,1%), salivary gland diseases (3,7%), periodontal diseases (2,7%), physical and chemical injuries (6,0%), Epithelial non infectious and non neoplasic diseases (6,7%), immunologic and allergic diseases (2,9%), pulp and apical diseases (9,8%). Proliferative non neoplastic lesions were the predominat diagnostic group (36,5%) followed by benignant and malignant neoplasms (22,4%). The fibrous hyperplasia was the most frequent lesion (33,2%) followed by squamous cell carcinoma (13,6%)and apical cyst (5,4%). The twelve most frequent lesions were responsible for 72,5% of the entire sample.